Zavtra . Tomorrow - Gryazev, Andrey (Gryazev, Andrey, 2012)
Verzio9 FF Submission. Duration: 01:30:00 Tomorrow is an unnerving portrait of Voina (War), a Russian anarchist art collective whose pranks and stunts have won them thousands of fans worldwide and support from the likes of Banksy. Vor (Thief) and his girlfriend Koza (Goat) lead the group on missions with their toddler, Kasper, strapped across their backs. The overturning of an empty police car brought the group acclaim in the international art scene while landing its core members with prison sentences and international arrest warrants. Andrey Gryazev incorporates the public images of Voina performances into his film, extending them with discussions, private scenes and television footage. What emerges is a film that is not just about Voina but also with, by and for them, with the director becoming part of the artgroup in the process. The rough-at-the-edges, dogme-style adventure quickly escalates into an unforgettable and thought-provoking drama.